Application of Waterfall Model In Development of Work Training Acceptance System - Hidayati, Nur; Sismadi, Sismadi (Universitas Nusantara PGRI Kediri, 2020)
Unemployment became a social problem for the community, so they could not meet their life needs. One cause because they do not have special skills, so it is difficult to get a job. Therefore, in every local government through the UPTD Balai Tenaga Kerja, it often conducts work training for those who need it. However, the system applied in the UPTD Bogor area is still conventional. Causing problems such as data readings are less obvious; form storage and documents are not neatly arranged, so some documents are missing and lost. It resulted in a loss for the participants who would participate in job training. So it takes the development of the system to solve the problem. To improve the existing system, that is from conventional to computerized. For the development of this system, it is necessary to take steps such as those in the waterfall model. The result of the development of this system is the design of a web-based work training acceptance system that can facilitate participants to access online in the selection of the desired work exercises, and the storage of documents will be stored neatly in a database.